1993
DOI: 10.1523/jneurosci.13-10-04146.1993
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor (BDNF) prevents the degeneration of medial septal cholinergic neurons following fimbria transection

Abstract: Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, supports the survival of developing basal forebrain cholinergic neurons in vitro and is retrogradely transported by cholinergic neurons of the medial septum and diagonal band following intrahippocampal injections in vivo. To substantiate a potential role for BDNF in the maintenance of forebrain cholinergic neurons in the adult brain, we assessed the ability of BDNF to sustain the phenotype of medial septal cholinergic neurons follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(106 citation statements)
references
References 52 publications
(82 reference statements)
1
105
0
Order By: Relevance
“…Free-floating sections were incubated in antiserum directed against 5-HT (Incstar Corp., Stillwater, MN), diluted 1: 15,000 (Mamounas et al, 1991). To assess the intracerebral distribution of the infused BDNE adjacent sections were incubated with a turkey anti-BDNF antibody (Amgen, Inc.) at a dilution of 1:7,500 (Morse et al, 1993). Bound immunoglobulin was visualized with the avidin-biotin-peroxidase method (Vector Laboratories, Burlingame, CA), using diaminobenzidine tetrachloride as the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Free-floating sections were incubated in antiserum directed against 5-HT (Incstar Corp., Stillwater, MN), diluted 1: 15,000 (Mamounas et al, 1991). To assess the intracerebral distribution of the infused BDNE adjacent sections were incubated with a turkey anti-BDNF antibody (Amgen, Inc.) at a dilution of 1:7,500 (Morse et al, 1993). Bound immunoglobulin was visualized with the avidin-biotin-peroxidase method (Vector Laboratories, Burlingame, CA), using diaminobenzidine tetrachloride as the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…NGF, infused intraventricularly, is able to prevent the loss of approximately 90% of the cholinergic neurons. Intraventricular and intraparenchymal infusions of BDNF also rescue septal Morse et al, 1993). We investigated whether FF/BDNF grafts placed directly in the septum could avert cholinergic neuronal degeneration following fimbria-fornix lesions, as do grafts of FF/NGF (Rosenberg et al, 1988).…”
Section: Effects Of Bdnf-transfected Fibroblast Grafts In Vivomentioning
confidence: 99%
“…Cholinergic neurons are rescued after axotomy following daily infusion of microgram amounts of BDNF Morse et al, 1993). However, the preventive effect of BDNF on degeneration of cholinergic cells after axotomy is significantly more pronounced when the trophic molecule is infused intraparenchymally rather than intraventricularly (Morse et al, 1993), presumably because intraparenchymal infusion circumvents the amount of BDNF that can bind to the truncated trkB receptor present on the ventricular wall. Because of the presence of the truncated form of the trkB receptor in the parenchyma as well, the proximity of the injection site is a crucial determinant.…”
Section: In Vivo Delivery Of Bdnf By Genetically Modified Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains possible that the development of the cholinergic phenotype occurs preferentially in cells that have settled down in a supportive environment or have established appropriate adhesive contacts on the slice. Other studies have reported expression of the cholinergic phenotype in dissociated cultures (Dreyfus, 1989;Hartikka and Hefti, 1988;Li et al, 1995;Nonomura et al, 1996;Shingai et al, 1990), however, the presence of exogenously applied neurotrophic factors or the presence of normal target cells is important for expression of the cholinergic phenotype and for survival (Dreyfus, 1989;Ha et al, 1996;Hartikka and Hefti, 1988;Li et al, 1995;Morse et al, 1993;Nonomura et al, 1996;Shingai et al, 1990). Grown in isolation, without target contacts or supplemental neurotrophins, the BFCNs do not thrive.…”
Section: Mechanisms Leading To the Non-random Distributionmentioning
confidence: 98%